66. Accuracy of neurophysiological tests in patients with neurological diseases and pelvic floor symptoms: Which tests for which patients?. Issue 12 (December 2017) - Turri, M.; Buono, R.; Basaldella, F.; Alessandrini, L.; Arcaro, C.; Tramontano, V.; Romito, S.; Squintani, G.
Abstract : To evaluate the sensitivity/specificity, positive and negative predictive values of neurophysiological tests in patients with neurological diseases and pelvic floor symptoms. From 2008 to 2016, among 92 outpatients who came to our attention for pelvic floor symptoms, 51 presented neurological disorders (32 with LMND, 17 with UMND and 2 with mixed clinical picture). 47 subjects with chronic pelvic pain served as controls. All subjects were submitted to neurological/perineal clinical evaluation and neurophysiological tests (EAS-CNEMG, PEPs, PAR or BCR, and sacral SSR). Upper and lower limits of normal values were collected and compared to patients' data. Sensitivity, specificity, positive and negative predictive values for each of the neurophysiological exams were also calculated together with any correlations with symptoms. CNEMG of EAS detected the highest sensitivity, specificity and predictive values, while sacral SSR showed lowest specificity and positive predictive value either in patients affected by LMND or UMND. Targeted protocols with different neurophysiological tests should be chosen on the basis of different neurological condition and level of damage rather than to apply the same generic protocol to all neurological patients with pelvic floor disorders.